ANALISIS PERMASALAHAN ANAK AUTIS DI SEKOLAH INKLUSI SMK NEGERI 9 KOTA PADANG - Nurul Aina Koto; Suryadi Suryadi; Triyono Triyono (Fakultas Tarbiyah dan Keguruan UIN Ar-Raniry, 2023)
This study aims to find out and explain the social abilities of autistic children, as well as to find out the efforts of teachers to overcome the difficulties of socializing autistic children at SMKN 9 Padang a school that has an inclusion class. This type of research uses qualitative methods with a case study approach. The research subjects were class IX students with autistic disorders. Data was collected using the method of observation, interviews, and documentation. Then to test the validity of the data using a credibility test. The credibility test was carried out using a triangulation technique. The results of interviews with counseling guidance teachers and with students who discussed the analysis of the problems of autistic children in inclusive schools SMK Negeri 9 Padang City and focused on autistic children in class XI Tataboga 3. Based on the results of research that had been carried out from interviews with key informants regarding